Insuficiencia jurídica del numeral 12, del art. 558, del código orgánico integral penal, tendiente a la forma como se debe regular la fijación de la pensión provisional de subsistencia, como una medida de protección adicional por violencia intrafamiliar - Collaguazo Yaguana, Ximena Valeria (2016)
The new Code of Criminal Integral, legal body which came into force in full on 10 August 2014, defines the offenses of violence against women or members of the family which mainly deal in the physical, psychological and sexual abuse. Thus, in the Art. 558 of the aforementioned legal precautionary and protective measures are established within which I would emphasize that established for violations of violence against women or members of the family, specifically paragraph 12 requiring the first paragraph as follows: "Where offenses of violence against women or members of the family concerned, in addition to the precautionary and protective measures provided for in this Code, the judge will set simultaneously or a pension which allows the survival of injured persons by aggression in accordance with the regulations on the matter, unless you already have a pension. " According to noted, the Act empowers the judge to apply a protective measure that concerns the livelihood of individuals who were harmed by the action of the perpetrator within the family; thus, in addition to injunctive or subsistence pension protection for those affected to be borne by the guilty will apply. As is evident in this legal paragraph states clearly not the way it should fix the living allowance for handicapped persons; that is, there are no exact parameters for fixing the living allowance and further to run.